Time and Soul From Aristotle to St. Augustine - Zachhuber, Johannes (CHRONOI, 2022)
In Book IV of his Physics, Aristotle asked whether time could exist without a soul that counts it. As a result, philosophers throughout antiquity tackled the problem of subjective time and its relation to the physical time of the cosmos. The present book gives an account of this debate. It analyses the contributions made by Aristotle and his Peripatetic followers but also discusses Neoplatonist and Early Christian authors including St. Augustine.